Linkages in the International Business Community: Accounting Evidence - Da Costa, Richard C.; Fisher, James; Lawson, William M. (Journal of International Business Studies, 1980)
This paper makes a case that accounting is a professional function in which activities depend on the needs of those business groups it serves. As the information needs of these separate national business groups converge, there will be precipitated a parallel growth of an internationalized accounting community. This study investigates two hypotheses about the international linkage between acounting practices and the information needs of the financial community.